PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 001 RANTAU PANJANG KIRI KECAMATAN KUBU BABUSSALAM - ', Wirdani; Marhadi, Hendri; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is to learn science is still low, the teacher uses conventional learning in which learners are placed as an object of study as a passive recipient of information. Students just listen penjelasn teachers, students afraid to respond to the lessons, due to fear of punishment. This is evident from the data collection instruments used sheets obseravasi student activity and teacher activity during the learning process takes place in class III SDN 001 Rantau Panjang Babussalam Left faction. It can also be seen in the percentage of test scores of students who reached the KKM (Minimum Criteria exhaustiveness) in class III SDN 001 Rantau Panjang Babussalam Left faction is 42.86% of the 21 students with an average value is 64.52. The KKM specified school is 72. Of these problems need to do action research by applying inquiry learning model. This study aims to determine whether the application of this inquiry learning model can improve learning outcomes third grade science students at SDN 001 Rantau Panjang Kiri Kubu Babussalam academic year 2015/2016 the number of students 21 students. This research was conducted in two cycles, cycle I and II, each consisting of 2 meetings with one daily tests. Instruments of data collection in this study is the observation sheet student activities, the activities of teachers and UH. Activities of students in the first cycle the average percentage of students amounted to 68.75% in cycle II increased to 85.41%. While the activities of teachers has also increased, verage percentage of the first cycle of 72.92% increase to 87.50% in the second cycle. The percentage of completeness on a base score of 42.86% with an average of 64.52 increased to 71.43% with an average of 76.19 in the first cycle, and then increased again in the second cycle into 90.48% with an average of 86, 67. It can be concluded that through the implementation of inquiry learning model can improve student learning outcomes SDN 001 class III Rantau Panjang Babussalam Left faction. Keywords: Inquiry Learning Model, Science Learning Outcomes